"Condensation of Meaning in the Stories of A Picture from the Archive by Hassan Bartal" - sendes.ahmed, sendes.ahmed (El Omda in Linguistics and Discourse Analysis, 2018)
This scholarly paper aims to examine one of the contemporary very short story experiences, namely the collection A Picture from the Archive by the Moroccan writer Hassan Bartal, from the perspective of how meaning is shaped through narrative condensation. Our choice of this approach allows us to address two interrelated levels: meaning and narrative structure, where the former necessitates the latter. The very short story requires the condensation of all narrative components, including space and time, characters, and language—an aspect that we observe in the author’s experimental approach, which establishes a new awareness in both writing and reading experience. This raises several questions: Has the writer’s vision expanded while achieving the primary characteristic of the very short story, namely extreme brevity? To what extent has the story reached its goals through the use of condensation as a key element in the formation of the very short story? And has this condensation achieved a sense of poetic quality in the story collection under study?